(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article discusses such tasks as the theoretical aspects of the emergence of free economic zones and their role in the economy of the state, the formation of free economic zones, the goals of creating and classifying free economic zones, the features of the emergence and development of tax regimes, the need for free economic zones in the development of the country. The analysis of the development of free economic zones and the existing tax regime, analysis of the legal framework for the creation and functioning of free economic zones.